British Medical Association and the National Health Service Bill (1946)
1946 1946 1940s 8 pages doctors. The introduction of a scheme available to the whole community will of itself exercise a very considerable influence in evening out medical distribution. The main problem which, in the Association's view, will remain unsolved by the introduction of a 100 per cent service, is the problem of the sparsely populated rural area. The method of extra inducement can and should be applied to solve the problem of the sparsely populated area, as it can be applied — if experience shows it to be necessary — to other areas. In addition, the Minister could retain the powers given in section 15 of the National Health Insurance Act, 1911 (and in section 37 of the Act of 1936), enabling appropriate arrangements to be made in areas where medical service is inadequate. The profession will willingly establish an advisory machinery for helping to assist incomers to practice to select areas where the need is greatest. What it is opposed to as both unnecessary and undesirable is the form of negative direction proposed by the Government. 26. It was the Government's proposals for control which, because of their anticipated effect on the capital value of practices, led it to put forward proposals for compensation. Clearly there should be full compensation for any adverse effect on capital values occasioned by the Government's proposals. But, in the Association's view, the Government should not proceed with proposals to control the distribution of doctors if improved distribution can be secured without such control. If the "control" proposals are not proceeded with, it will be unnecessary to interfere with existing arrangements for the buying and selling of practices. The profession can and will make possible by its organization the entry or re-entry of demobilized practitioners to general practice under terms which are not onerous. Clearly the proposal to abolish the buying and selling of practices is a crucial issue. Already the profession has expressed the view "that it is in the national interest and essential to the independence of the profession that doctors should continue to own the goodwill of their practices". The three proposals (a) to abolish buying and selling, (b) to institute basic salaries, (c) to control the distribution of doctors, considered either separately or as related parts of the plan, would take the profession much nearer the whole-time state-salaried service to which it is so strongly opposed. 27. It is understood that a substantial proportion of general practitioner remuneration will be derived from basic salary. The Association can find no justification for this proposal. It desires that the main, if not the only, element in general practitioner remuneration should be the choice of the individual doctor by the individual patient. The basic salary proposal, particularly if the proportion of the total remuneration is substantial, will lead to whole-time salaried service — something to which the profession is wholly opposed. It believes that in the future, as at present, there will need to be an appropriate proportion of assistants to principals in general practice, those assistants being employed by principals. It would be appropriate to establish agreed general salaries for assistants. It would be reasonable to require that a practitioner shall not become a principal in the new service until he had served for a prescribed period of time as an assistant. When he becomes a principal, his remuneration should be related to the number of patients on his list. 28. If the Government proposes to pay basic salary only when a certain minimum number of patients have chosen the doctor, its proposal is superfluous. If it proposes to pay a basic salary to a practitioner entering the public service, however small the number of patients who are on his list, then the proposal is extravagant. AMOUNT OF COMPENSATION 29. After discussion between the Ministry of Health and the Compensation Subcommittee of the Negotiating Committee the following letter was sent to the Minister: March 8th, 1946. Dear Mr. Bevan, The Compensation Subcommittee of the Negotiating Committee has entered into discussions with the Ministry on the question of compensation, without accepting the policy from which the necessity for compensation arises. The medical profession is in no way committed to the policy of abolishing the custom of buying and selling goodwill. Indeed it has in the past expressed its opposition to this policy. Important principles affecting the freedom of the medical profession are involved, and the amount of money offered by the Government in compensation is irrelevant. The Government's proposals must be considered as a whole and not merely in terms of finance. The view of the Subcommittee is that if the Government persists in this policy, and Parliament approves, then the sum of £66,000,000 which the Government, after negotiations with the Subcommittee, now offers may, on the evidence available, be taken to represent the aggregate capital loss involved in respect of the goodwill of general practices. The Compensation Subcommittee understands that this sum of £66,000,000— (a) is based on the Government's estimate that 17,900 principals will enter the National Health Service; (b) will not be subject to increase if in fact more than 17,900 principals so enter; (c) will be subject to reduction if the number of principals so entering is below 17,700; the reduction for each principal in defect of 17,700 to be 1/17,900 of £66,000.000. Yours sincerely, (Signed) CHARLES HILL, Secretary. The Right Hon. Aneurin Bevan, M.P. SOME OTHER POINTS Civil Rights of Doctors 30. It should be secured in the Bill that doctors who participate in the National Health Service are 7 292/847/4/40